Impact of Service Quality on Customer Satisfaction, Loyalty, and Commitment in the Indian Banking Sector - Hazra, Sandip Ghosh; Srivastava, Kailash B. L. (Indian Journal of Marketing, 2010)
Service quality is a critical determinant of competitiveness for establishing and sustaining satisfying relationships with customers. Service marketers have realized that competition can be well managed by differentiating through quality. A customer-minded corporate culture, an excellent service-system design, and effective use of technology and information are crucial to superior service quality.